2009
DOI: 10.1098/rstb.2009.0085
|View full text |Cite
|
Sign up to set email alerts
|

Breathing withPhox2b

Abstract: In the last few years, elucidation of the architecture of breathing control centres has reached the cellular level. This has been facilitated by increasing knowledge of the molecular signatures of various classes of hindbrain neurons. Here, we review the advances achieved by studying the homeodomain factor Phox2b, a transcriptional determinant of neuronal identity in the central and peripheral nervous systems. Evidence from human genetics, neurophysiology and mouse reverse genetics converges to implicate a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 55 publications
(68 reference statements)
1
42
0
2
Order By: Relevance
“…The retrotrapezoid nucleus/parafacial respiratory group (RTN/pFRG) contains glutamatergic neurons expressing the transcription factor paired-like homeobox 2b (Phox2b) [16,25,71,80], many of which are rhythmically active intrinsically in perinatal rodents [70,71], and is called the pFRG. In adults, these neurons (called RTN) are tonically active [25,81] or respiratory-modulated [66], which may reflect developmental transformation [77].…”
Section: Figurementioning
confidence: 99%
“…The retrotrapezoid nucleus/parafacial respiratory group (RTN/pFRG) contains glutamatergic neurons expressing the transcription factor paired-like homeobox 2b (Phox2b) [16,25,71,80], many of which are rhythmically active intrinsically in perinatal rodents [70,71], and is called the pFRG. In adults, these neurons (called RTN) are tonically active [25,81] or respiratory-modulated [66], which may reflect developmental transformation [77].…”
Section: Figurementioning
confidence: 99%
“…This has been bolstered by data of Guyenet et al (2005), who have shown that the RTN, which as noted earlier spatially overlaps the pFRG, appears to provide a fundamental chemosensory drive to the VRC. Furthermore, developmental studies show that RTN/pFRG cells embryologically have a transcription factor (Phox2b) expression phenotype and that deletion of these cells in mutant mice causes a congenital central hypoventilation-like syndrome associated with irregular breathing, lack of responsiveness to hypercapnia and fatality at birth (Dubreuil et al 2009).…”
Section: Other Oscillatory Mechanisms In the Networkmentioning
confidence: 99%
“…Infants with less severe CCHS can display diaphoresis, cyanosis during sleep, and tachycardia. Others may have unexplained apnea, even die, and be categorized as having sudden infant death syndrome (SIDS) [65,66]. Patients also have symptoms related to the autonomic nervous system abnormalities described earlier.…”
Section: Clinical Picturementioning
confidence: 99%